Pengaruh Kepemimpinan Karismatik, Lingkungan Kerja dan Disiplin Kerja Terhadap Semangat Kerja Pegawai LPD Kecamatan Tampaksiring - Oktaviani, Ni Wayan Ema; Ayu Wimba, I Gusti; Putra Astawa, I Putu (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2023)
Morale is closely related to employee performance within a company. Morale can be generated by charismatic leadership, work environment, and work discipline. The population used in this study were all employees at the Village Credit Institution, Tampaksiring District, with a sample of 67 respondents who were determined using the slovin formula. The analytical technique used in this research is multiple linear regression analysis. Based on the results of the study, it can be seen that: Charismatic Leadership, Work Environment, and Work Discipline have a positive and significant effect partially or simultaneously on Work Morale. The magnitude of the influence of the independent variable on morale is 90.8%. Seeing these results, the leadership at the LPD (Village Credit Institution) of Tampaksiring District in the future must be more assertive, obey the rules, and regulate how to speak so that later they can look more authoritative, and can be used as role models by their subordinates.